CORRELATION OF CYTOKINE LEVELS IN CHILDREN WITH JUVENILE RHEUMATOID ARTHRITIS (JRA) AGED 7 TO 14 YEARS (E Global Congress, 2024)
Juvenile rheumatoid arthritis (JRA) is one of the most common chronic inflammatory joint diseases in children, leading to significant immune system changes. Cytokines play a key role in the pathogenesis of JRA, and their levels may serve as prognostic markers for disease activity.